1996
DOI: 10.1111/j.1445-5994.1996.tb00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C genotypes in Australian haemophilia patients

Abstract: Despite patients with haemophilia being exposed to multiple HCV genotypes, it appears that there is no selection advantage of one genotype over another. Australian haemophilia patients with HCV have a different genotype distribution to that reported in other countries and care should be observed in interpreting non Australian studies concerning HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Previous prevalence surveys of chronic HCV infection in Australia between 1997 and 2000 resulted in reported ranges of 20% to 38% for genotype 3 and 52% to 65% for genotype 1 (18)(19)(20)(21)(22)(23)(24). In contrast to those studies, the findings reported here indicate an apparent increase in the transmission of genotype 3 (51% of incident infections).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous prevalence surveys of chronic HCV infection in Australia between 1997 and 2000 resulted in reported ranges of 20% to 38% for genotype 3 and 52% to 65% for genotype 1 (18)(19)(20)(21)(22)(23)(24). In contrast to those studies, the findings reported here indicate an apparent increase in the transmission of genotype 3 (51% of incident infections).…”
Section: Discussioncontrasting
confidence: 56%
“…Genotype 4 is prevalent in the Middle East and Africa, and high prevalences of genotypes 5 and 6 have been reported in South Africa and Asia, respectively (17,18). The genotypes most commonly reported among chronically infected individuals in Australia are genotypes 1 (52% to 65%) and 3 (20% to 38%), with low prevalences of genotypes 2, 4, and 6 (approximately 5% to 9%, 0% to 6%, and 0.6% to 2%, respectively) (19)(20)(21)(22)(23)(24)(25). It should be noted, however, that these prevalence surveys were conducted in the 1990s and predominantly screened chronically infected individuals who had likely contracted the virus years to decades prior to testing; therefore, the results of those studies do not necessarily represent the viruses currently being transmitted (26).…”
mentioning
confidence: 99%
“…Fifty per cent of subjects were exposed to HCV via contaminated blood clotting factors (male subjects with X-linked Haemophilia) whereas the remaining 50% represented individuals that acquired HCV infection predominantly via intravenous drug use (IDU). For subjects with Haemophilia modelling shows the likelihood of infection with more than one viral strain [ 15 ] and data from studies on intravenous drug users (IVDU) show that the level of repeat exposure to diverse viral strains is high [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…One important characteristic in this group of patients is that a significant proportion has a mixed-genotype infection due to multiple exposures to contaminated blood products over a period of years [ 24 ]. Overall, HCV genotype 1 seems to be the dominant one (Iran 72.7%, Australia 65%, USA 46.2%) followed by genotype 3 (27.3%, 30% and 42% respectively) [ 25 - 27 ].…”
Section: Epidemiologymentioning
confidence: 99%